Hyperbaric pressure combined with refrigeration vs conventional refrigeration: Ripening and senescence processes of tomatoes - Inestroza-Lizardo, Carlos; da Silva, Josiane Pereira; Pinzetta Junior, José Sidnaldo [UNESP]; Mattiuz, Ben-Hur [UNESP] (Elsevier, 2021)
This study aimed to evaluate whether the hyperbaric pressure combined with refrigeration (200, 400, 600, and 800 kPa at 13 ± 1°C) for 4 or 8 d, promotes any improvement compared to conventional refrigeration (13 ± 1°C to 100 kPa), in the regulation of the ripening and senescence processes of tomatoes. Fruit stored for 8 d under hyperbaric pressure of 600 and 800 kPa showed reduced respiratory rate during storage, delayed climacteric peak, lower weight loss (74 %), and greater firmness (25 %) compared to the tomatoes stored under conventional refrigeration. Moreover, storage at 800 kPa led to an increase in the CAT and a decrease in POD enzymatic activities. Our findings show that the hyperbaric pressure at 600 and 800 kPa combined with refrigeration was more efficient than conventional refrigeration, delaying the ripening process, and increasing the tomatoes shelf life.
Keywords: Antioxidant enzymes; Commercial parameters; Ethylene; Lycopene; Physiological metabolism; Respiratory rate